The Effect of Profitability, Managerial Ownership and Dividend Policy on Corporate Value LQ-45 Companies Listed on The Indonesia Stock Exchange During The 2020 – 2023 Period - Sonya Kristy Br Brahmana; Dimitha H P Purba; Mitha Christina Ginting; Ivo Maelina Silitonga (Jurnal Ilmiah Accusi, 2025)
The purpose of this study is to analyze the influence of profitability, managerial ownership, and dividend policy on firm value. The research problem is formulated as follows: whether profitability, managerial ownership, and dividend policy influence firm value. The sample used was 14 companies. The data used in this study were obtained from the annual financial reports of LQ-45 companies for the years 2020-2023. The population of companies in this study consisted of 45 LQ-45 companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. A total of 14 samples were used in this study, with sample selection using a purposive sampling method. Data analysis used descriptive statistics, classical assumption tests, and hypothesis testing with regression methods using SPSS 26. This type of research is a quantitative correlational study, which is intended to examine the relationship between variables. The analysis technique used was multiple linear regression. The results showed that profitability significantly influences firm value, managerial ownership significantly influences firm value, while dividend policy does not affect firm value. Profitability, managerial ownership, and dividend policy variables simultaneously have a significant effect on company value in LQ-45 companies listed on the Indonesia Stock Exchange for the 2020-2023 period